1985
DOI: 10.1111/j.1471-4159.1985.tb07149.x
|View full text |Cite
|
Sign up to set email alerts
|

Free and Conjugated Amines in Human Lumbar Cerebrospinal Fluid

Abstract: Significant amounts of acid-hydrolyzable conjugates of 3,4-dihydroxyphenylethylamine, norepinephrine, and 5-hydroxytryptamine were detected in lumbar CSF from 22 awake unpremedicated healthy individuals. In the CSF samples, the amounts of conjugated amines almost always exceeded the amounts of free amines, but were less than the amounts of the acid metabolites 3,4-dihydroxyphenylacetic acid, homovanillic acid, and 5-hydroxyindoleacetic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…26 showing a decrease in conjugated CSF-DA concentrations in successive samples of human lumbar CSF covering a total amount of 90 ml. Moreover slight support for our results is found in the studies by Sharpless et al 2~ Tyce et al 25 suggesting higher levels of conjungated DA at the lumbar than at the ventricular level. Moreover, the high correlation between L-CSF-DA and V-CSF-DA suggests that DA concentrations measured at the lumbar levels states the concentrations measured at the ventricular level.…”
Section: Discussionsupporting
confidence: 57%
“…26 showing a decrease in conjugated CSF-DA concentrations in successive samples of human lumbar CSF covering a total amount of 90 ml. Moreover slight support for our results is found in the studies by Sharpless et al 2~ Tyce et al 25 suggesting higher levels of conjungated DA at the lumbar than at the ventricular level. Moreover, the high correlation between L-CSF-DA and V-CSF-DA suggests that DA concentrations measured at the lumbar levels states the concentrations measured at the ventricular level.…”
Section: Discussionsupporting
confidence: 57%
“…Initially, a considerable amount of acid-hydrolysable conjugates of dopamine, norepinephrine (NE) and 5-HT were detected in lumbar CSF of normal individuals. The amounts of conjugated amines were small in comparison to the amounts of homovanillic acid and 5-hydroxyindoleaceticacid [9]. In a further study performed with CSF from humans and ventriculocisternal perfusion of African green monkeys found that the sulphates of NE, dopamine and 5-HT are present in the CSF of laboratory animals and humans.…”
Section: Literature Evidence Related To 5-ht-so 4 Appearance In Animamentioning
confidence: 92%
“…Homovanillic acid (HVA) and 5-hydroxyindoleacetic acid (5HIAA) were measured after deproteinization with perchloric acid by high-performance liquid chromatography with electrochemical detection (Palfreyman et al, 1982;Silverstein et al, 1984;Tyce et al, 1985). Twenty microliters of the supernatant were injected directly into the system which included a precolumn (BST-GMK) and a 4 x 250 mm, 7 gm reverse phase column (Separon C-18).…”
Section: Methodsmentioning
confidence: 99%